Vom Recht des Proselyten in LXX-Maleachi 3:5 - Dafni, Evangelia G (Verbum et ecclesia, 2021)
On the right of the proselyte in LXX-Malachi 3:5. This article deals with Malachi 3:5 from the perspective of language theology. An attempt is made to answer the questions of how the LXX translator of the Malachi book came up with the reading ‘bend the right of the proselyte’, how this reading can be correctly interpreted and in which way it relates to the question of proselyte law and theology, the language of the Septuagint. Intradisciplinary and/or interdisciplinary implications: The focus falls in the contextual-hermeneutical study in the translation in the Septuagint of Malachi 3:5 in the Old Testament, posing the question on how the translator conceived of the right of the proselyte and how it can best be understood. The interdisciplinarity of the article touches on both the Hebrew Bible and the Septuagint (LXX) texts.